Adiponectin Attenuates Angiotensin II-Induced Vascular Smooth Muscle Cell Remodeling through Nitric Oxide and the RhoA/ROCK Pathway - Nour-Eldine, Wared; Ghantous, Crystal M.; Zibara, Kazem; Dib, Leila; Issaa, Hawraa; Itani, Hana A.; El-Zein, Nabil; Zeidan, Asad (Frontiers in Pharmacology, 2016)
INTRODUCTION: Adiponectin (APN), an adipocytokine, exerts protective effects on cardiac remodeling, while angiotensin II (Ang II) induces hypertension and vascular remodeling. The potential protective role of APN on the vasculature during hypertension has not been fully elucidated yet. Here, we evaluate the molecular mechanisms of the protective role of APN in the physiological response of the vascular wall to Ang II. METHODS AND RESULTS: Rat aortic tissues were used to investigate the effect of APN on Ang II-induced vascular remodeling and hypertrophy. We investigated whether nitric oxide (NO), the RhoA/ROCK pathway, actin cytoskeleton remodeling, and reactive oxygen species (ROS) mediate the anti-hypertrophic effect of APN. Ang II-induced protein synthesis was attenuated by pre-treatment with APN, NO donor (SNAP), or cGMP. The hypertrophic response to Ang II was associated with a significant increase in RhoA activation and vascular force production, which were prevented by APN and SNAP. NO was also associated with inhibition of Ang II-induced phosphorylation of cofilin. In addition, immunohistochemistry revealed that 24 hr Ang II treatment increased the F- to G-actin ratio, an effect that was inhibited by SNAP. Ang II-induced ROS formation and upregulation of p22phox mRNA expression were inhibited by APN and NO. Both compounds failed to inhibit Nox1 and p47phox expression. CONCLUSIONS: Our results suggest that the anti-hypertrophic effects of APN are due, in part, to NO-dependent inhibition of the RhoA/ROCK pathway and ROS formation.